POLYA MODEL THROUGH MATHEMATICAL ROBOT MEDIA (ROMI) FOR STORY SOLVING IN GRADE 1 STUDENTS OF SD JUARA SURABAYA - Furri Kurnia Aditama; Arya Setya Nugroho; Eka Rosita (Sahabat Publikasi, 2023)
This research was motivated by the low ability of students to solve story problems in grade 1 of SD Juara Surabaya. Students experienced difficulties in this study motivated by the low ability of students to solve story problems in grade I SD Juara Surabaya. Students have difficulty solving addition and subtraction material story problems. The objectives of this study are: 1) To determine the application of the Polya model in improving the ability to solve story problems in Mathematics learning with the Polya model through the Mathematical Robot (ROMI) media in grade I students of SD Juara Surabaya. 2) To find out the activities of teachers and students in improving the ability to solve story problems in Mathematics learning with the Polya model through the medium of Mathematical Robot (ROMI) in grade I students of SD Juara Surabaya. This class action research uses the Kurt Lewin model which is carried out as many as 2 cycles. Each cycle consists of 4 stages: planning, action, observation, and reflection. The subjects of this study were grade I students of SD Juara Surabaya consisting of 21 students. The action taken is to apply the Polya model. Data collection techniques in the form of observation, angketization, tests and documentation. The results showed that: 1) The ability to solve story problems of grade I students of SD Juara Surabaya after using the Polya model with ROMI media in mathematics learning has increased very significantly. The ability to solve students' story problems increases with each cycle. In the pre-cycle activity, 23.80% of students were completed and 76.2% were incomplete. In the first cycle, 47.6% of students were completed and 52.3% were incomplete. Meanwhile, in the second cycle as many as 85.2% of students who were completed and 14.8% of students who were not completed.2 2) The average score of student worksheets on the stories of grade I students of SD Juara Surabaya after using the Polya model with ROMI media in mathematics learning experienced a good increase. In the pre-cycle activity, the average score of the students' worksheets on grade I students' story questions was 74. The average score of the results of working on student worksheets on grade I students' story questions in cycle I is 80. While the average score of student worksheets on grade I students' story questions is 93 in cycle II. 3) Application of Polya model using ROMI media in improving The ability to solve story problems of grade I students of SD Juara Surabaya in learning Mathematics has been successful.